2014
DOI: 10.1007/s11357-014-9717-1
|View full text |Cite
|
Sign up to set email alerts
|

Phycoerythrin extends life span and health span of Caenorhabditis elegans

Abstract: In the present study, we tested the antioxidant activity of phycoerythrin (PE, an oligomeric light harvesting protein isolated from Lyngbya sp. A09DM) to curtail aging effects in Caenorhabditis elegans. Purified PE (100 μg/ml) dietary supplement was given to C. elegans and investigated for its anti-aging potential. PE treatment improved the mean life span of wild type (N2)-animals from 15±0.1 to 19.9±0.3 days. PE treatment also moderated the decline in aging-associated physiological functions like pharyngeal p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
38
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 52 publications
(44 citation statements)
references
References 49 publications
4
38
0
2
Order By: Relevance
“…The altered regulation of the major players in this pathway, daf-2, daf-16, and age-1 suggested that the changes in the lifespan of the host was under the influence of the above pathway. The genes daf-2 and age-1 are negative regulators of lifespan whereas daf-16 positively regulates lifespan (Sonani et al 2014). In the present study, as the time of exposure increased, the level of expression of daf-2 and age-1 were also increased; in turn, the expression of daf-16 decreased.…”
Section: Discussionsupporting
confidence: 52%
See 3 more Smart Citations
“…The altered regulation of the major players in this pathway, daf-2, daf-16, and age-1 suggested that the changes in the lifespan of the host was under the influence of the above pathway. The genes daf-2 and age-1 are negative regulators of lifespan whereas daf-16 positively regulates lifespan (Sonani et al 2014). In the present study, as the time of exposure increased, the level of expression of daf-2 and age-1 were also increased; in turn, the expression of daf-16 decreased.…”
Section: Discussionsupporting
confidence: 52%
“…In the current scenario, extending lifespan without extending health will not fulfill the goal of aging research. Some of the recent studies show that phycoeryhtrin isolated from a marine cyanobacterium (Sonani et al 2014) and cranberry extract (Guha et al 2013) can extend the healthspan of nematode along with extending lifespan. Here, we have used pharyngeal pumping and egg laying ability of C. elegans as the phenotypic readouts to measure healthspan.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Currently, our research group is working on the topic -'Is PBP's antioxidant virtue can be explored to alleviate aging and associated abnormalities?' We have reported that the PE, one of the PBPs having antioxidant nature, efficiently moderates the progression in physiological dysfunctions and molecular mechanism associated with aging in Caenorhabditis elegans (C. elegans) [6,40]. PE feeding also confers the better stress tolerance in C. elegans under thermo-as well as oxidative stress [40].…”
Section: Pbps As Anti-aging Moleculesmentioning
confidence: 99%